Resistance in the data-driven society - Stefania Milan (Internet Policy Review, 2024)
Individuals and groups increasingly seek to resist the harms and risks of a data-driven society. This essay explores the possibility of individual and collective resistance vis-à-vis datafication, drawing on examples from across the globe. It shows how infrastructure, political agency, and tactics have changed in response to datafication. It reviews six resistance tactics, distinguishing between "defensive resistance" and "productive resistance": self-defence, subversion, avoidance, literacy, counter-imagination, and advocacy campaigning. Investigating them offers insights on the ability of social actors to contribute to innovation in mobilising practices amidst intrusive surveillance.
Keywords: 300; Infrastructure; Agency; Datafication; Resistance; Tactics